Influence of curing type on the filler effect of ground scheelite residue in cementitious matrix - Costa, Carolina de Castro; Barros, Samea Valensca Alves (Latin American Journal of Energy Research, 2025)
The prerogative of achieving Sustainable Development Goal number 12 by 2030 encourages researchers to promote the guarantee of sustainable consumption and production patterns for the Architecture, Engineering, and Construction Industry. This involves analyzing the properties of scheelite waste due to the large volume generated in the Currais Novos/RN region as a result of tungsten production, mainly for the export market, and seeking to find a suitable destination for it. However, there are gaps in the literature regarding the technical feasibility of using this ground residue as a partial replacement for conventional aggregate in the production of cementitious matrices. In this context, this research aimed to verify the filler effect of ground and sieved scheelite residue in mortars. The methodological procedures for processing the waste material used consisted of using grinding and sieving techniques. The preparation of the alternative mortars was carried out using cylindrical molds with dimensions of (50 X 100) mm with partial replacement levels to the conventional aggregate of 10% and 15%. The results obtained demonstrated the technical feasibility regarding the parameter determined in this investigation. Furthermore, increasing the substitution of sand with the beneficiated residue promoted a filler effect, and wet curing achieved better results for unconfined compressive strength. Moreover, the values ​​were within those established by NBR 13281-2 (ABNT, 2023) for use in mortar for laying masonry walls and for completing masonry.